Africanisation of worship in the Langa Moravian church : liturgy in a new key - Kronenberg, Joy Faith (Not Specified, 2023)
This thesis explores "inculturation as it has and has not taken place in the Moravian Church in general and specifically at Langa where the writer has been a probation minister from 1998- 1999 and an ordained minister from 1999 onwards. It explores the amelioration of the present undesirable situation. It is recognised that life is not static but dynamic, that worldviews change, and human identity is reconstructed. So, moves are indicated that will assist to transform the attitudes of the faithful. We need to aim for an atmosphere of discussion and shared decision making that is for active participation in leadership and genuine collegiality in a Church which no longer insists on its own monochrome culture but exists as a multicultural family of sisters and brothers in communion. This study seeks to examine the socio-literary function of the theme of this thesis Africanisation within the Langa Moravian Congregation: Liturgy in a New Key and will adopt a socio-linguistic perspective. The use of this approach emanates from the fact that this study is concerned about the language and anti-language as practised in the Church and society. Social scientific methods are a departure from the positivist empiricism of the historical critical method With the imposition of one religion over another and the unfounded assumption that one is universal, single, normative and a criterion according to which the world religions ought to be judged, the missionaries committed a social sin against the whole world; that human beings, in general and Africans in particular were judged as either cultured or uncultured, civilised or uncivilised, human or savages, through the Christian religion; that all other religions ought to be judged as either being true, false, authentic and /or revealed through Christianity. The term 'imposition' refers to a method or process by which doctrines, religious customs, morals and ways of praying and acting are brought from the outside, from a foreign or alien culture and tradition and imposed or forced upon the new cultures. It shows no appreciation, no respect or regard for the values, customs and religious traditions of the group that is the object of mission. The first missionaries who came to South Africa infiltrated all sectors of the social infrastructure and became saviour gods in their own right, while at the same time they did everything within their power to displace African culture and Westemise the Africans. We are made to live in a network of interdependence with one another, with God and with the rest of God's creation. As we say in Xhosa Umntu ngumntu ngabantu- a person is a person through other persons. A solitary human being is a contradiction in terms. A totally self-sufficient human being is ultimately subhuman. This is also true of the different nations: that one people has particular gifts, a distinct world view, a cultural ethos, which is not necessarily better or superior to those of other people. So we find that Africans have a strong sense of community, of belonging, whereas Occidentals have in contrast a strong sense of the individual person. These attributes, in isolation and pushed to extremes have weaknesses Within the wider perspective of sociolinguistics, the model that used here is that of Language and Anti-language. An antilanguage is a language that is generated by an anti-society, that is, a social collectively which is embedded in another society but feels threatened or alienated by the dominant conventional norms of the wider society and therefore sees itself as a conscious alternative to it. The language generated by such a social collectively serves to express its alternative view of social reality and becomes a mode of resistance to the prevailing social order. I hope this study will re-emphasise my conviction that the Church remains the terrain as well as the weapon of struggle for the liberation of the poor, marginalised, oppressed and exploited.